(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Juvenile delinquency has emerged as a substantial societal concern, prompting various nations, including the Philippines, to institute protective measures for young offenders to shield them from severe penalties. In this context, the municipality of San Gabriel in the Province of La Union has garnered attention due to its rapid development. This growth prompted researchers to delve into the municipality’s familial and juvenile delinquency landscape. A mixed methods research design was employed to comprehensively investigate the intricate relationship between family dynamics and juvenile delinquency in San Gabriel, La Union. This approach harmoniously combined qualitative and quantitative methods within the same study, allowing for a more holistic exploration. The study’s focus extended to various aspects of family and juvenile delinquency, encompassing family structure, socio-economic standing, birth order within the family, the nature of committed crimes, frequency of apprehensions, and the educational background of juvenile delinquents. To ascertain the link between family status and juvenile delinquency within San Gabriel, La Union, the researchers applied the chi-square formula, facilitating a statistical examination of the relationship. Over ten years, from 2010 to 2020, the Municipality Social Welfare and Development of San Gabriel, La Union, documented 13 cases, while the Philippine National Police of the same municipality recorded 9 cases. The research outcomes unveiled noteworthy insights regarding the demographic backgrounds of juvenile delinquents. Most young offenders originated from nuclear family setups and experienced lower socio-economic conditions. In addition, a pattern emerged whereby a significant portion of the juvenile delinquents were involved in cases of rape and violations of Republic Act 9165, which pertains to illegal drugs. Delving deeper into the statistical analysis, it was determined that the type of crime committed, frequency of apprehensions, birth order within the family, and educational attainment did not exhibit a statistically significant connection with the family status of the juvenile delinquents. This finding underscores juvenile delinquency’s intricate and multifaceted nature, suggesting that it cannot be attributed solely to a single factor, such as family structure. In conclusion, this research sheds light on the link between family dynamics and juvenile delinquency and emphasizes the phenomenon’s complexity. Through a meticulous blend of qualitative and quantitative methods, the study underscores the importance of a comprehensive approach to understanding and addressing the intricacies of juvenile delinquency within the evolving context of a fast-developing municipality like San Gabriel, La Union.